Understanding the Implementation of Small-Scale Water and Other Infrastructure Developments in Small Islands in Indonesia: A Rapid Survey in Bintan and Mandeh Islands - Yandri, Pitri; Kusumartono, FX Hermawan; Rianto, Nanang; Putri, Intan Adhi Perdana (Forum Geografi, 2020)
Access to clean water and electricity is one of the sustainable development agendas being addressed worldwide. However, people living on small islands scattered throughout Indonesia still face difficulties in accessing clean water and electricity. In an effort to overcome this problem, the Indonesian government and other donors are building small-scale clean-water infrastructure in a number of these small islands. Other infrastructure, such as electricity supply, has also been developed in a number of places. The infrastructure framework for these works is directed toward community-based management efforts. However, various problems have emerged after the construction of these facilities. Instead of achieving increased community participation in their management, the opposite occurs. This article investigates this situation using a rapid survey of communities in Bintan Island and Kapo-Kapo Island in the Mandeh Waters area, and finds that the development of small-scale infrastructure has a different impact on the two regions observed. An elaboration of various field findings is presented in detail in this article.